From Basic Research to New Tools and Challenges for the Genotoxicity Testing of Nanomaterials - FESSARD, Valérie; Nesslany, Fabrice (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue presents studies on the genotoxicity of nanomaterials. Although nanomaterials provide multiple benefits in a wide range of applications, challenges remain in addressing strong concerns about their risks to the environment and human health. As a result of inconsistencies among published results and diverging conclusions, the understanding of nanomaterial exposure and toxicity remains unclear. Determining whether these materials cause DNA damage-the first step in carcinogenesis-must be a priority in testing. In this book, readers will find recent publications on the genotoxic response to a broad range of nanomaterials, the impact of physico-chemical characteristics, safe-by-design and new developed tools.